Życiorysy równoległe resortowych „dam”: Julii Brystiger, Marii Wiernej i Heleny Wolińskiej. Przyczynek do historii kobiet-komunistek w Polsce - Sztama, Paweł (Komunizm: System - Ludzie - Dokumentacja, 2023)
This study aims to compare the biographies of three women who made brilliant careers in important institutions of communist Poland. Julia Brystiger worked for over a decade in the repressive apparatus, Maria Wierna for several decades in the communist diplomacy, and Helena Wolińska, in the Stalinist period of the People’s Republic of Poland, functioned in the structures of the Citizen’s Militia, and later the Chief Military Prosecutor’s Office. All the women discussed in this article not only performed managerial functions. Above all, they were figures with enormous connections, who had a considerable influence on the activities of the departments in which they worked. The article shows, in a comparative way, the life path of each of them, from their birth, through education, activities in different periods, until their death.